2017
DOI: 10.1111/gcb.13676
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is predicted to alter the current pest status of Globodera pallida and G. rostochiensis in the United Kingdom

Abstract: The potato cyst nematodes Globodera pallida and G. rostochiensis are economically important plant pathogens causing losses to UK potato harvests estimated at £50 m/ year. Implications of climate change on their future pest status have not been fully considered. Here, we report growth of female G. pallida and G. rostochiensis over the range 15 to 25°C. Females per plant and their fecundity declined progressively with temperatures above 17.5°C for G. pallida, whilst females per plant were optimal between 17.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
3
47
0
2
Order By: Relevance
“…Globodera rostochiensis and Globodera pallida originate from S. America and are known pests of other members of the Solanaceae family including tomatoes and woody nightshade [39]. These nematodes are classiied as quarantine pests in a number of countries including the U.S. and an estimated £ 50m year in proits are lost each year in the U.K. [40]. Other major plant-parasitic nematodes of potato include root-knot nematodes (Meloidogyne spp.…”
Section: Potatomentioning
confidence: 99%
“…Globodera rostochiensis and Globodera pallida originate from S. America and are known pests of other members of the Solanaceae family including tomatoes and woody nightshade [39]. These nematodes are classiied as quarantine pests in a number of countries including the U.S. and an estimated £ 50m year in proits are lost each year in the U.K. [40]. Other major plant-parasitic nematodes of potato include root-knot nematodes (Meloidogyne spp.…”
Section: Potatomentioning
confidence: 99%
“…The model was sufficient to capture the main characteristics of the data and the projections made provide a germinal risk assessment for GB that could be improved with more data. It should also be noted that a recent study concluded that increased soil temperatures associated with climate change may reduce the pest status of G. pallida in GB (Jones et al ., ). The authors found that reproductive success of G. pallida decreased with temperature from 15 to 25 °C, which was the full range of temperatures tested.…”
Section: Discussionmentioning
confidence: 97%
“…Females were observed on the roots from week 4 onwards at Harper Adams with relatively warmer soil temperatures as found by Jones et al . (). It is probable that a second generation developed, as both juveniles and females were observed at harvests 5 (week 20) and 6 (22 weeks), although the possibility that the late females observed in the field samples may have resulted from a delayed initial hatch cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…In the last century, global temperatures have been increasing due to climate change and the effect of this trend on crop losses due to plant pests and diseases, including soil dwelling organisms such as PCN, is of concern (Ellenby & Smith, ; Stanton & Sartori, ; Munir et al ., ; Ebrahimi et al ., ; Jones et al ., ; Skelsey et al ., ). Recently Jones et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation